Cover Feature: Photobioanodes Based on Nanoimprinted Electrodes and Immobilized Chloroplasts (ChemElectroChem 2/2022). Issue 2 (16th December 2021) - Aleksejeva, Olga; Nilsson, Nicklas; Genevskiy, Vladislav; Thulin, Kristian; Shleev, Sergey
Abstract : The Cover Feature demonstrates a low potential highly capacitive dual‐feature anode composed of nanostructured (using nanoimprint lithography – an industry‐scale throughput, cost‐effective and versatile method) gold electrodes modified with chloroplasts and poly(3, 4‐ethylenedioxythiophene). More information can be found in the Article by O. Aleksejeva et al .